O trabalho linguístico na alfabetização e o desenvolvimento das competências metalinguísticas - Almeida, Simonny de Jesus Flores de (Brasil, 2025)
The present study aimed to investigate the interrelations between metalinguistic skills and competencies in the process of literacy and reading acquisition. Over the years, the teaching and learning of reading and writing have presented many challenges for both literacy educators and learners, as linguistic work requires an interdisciplinary approach involving various language skills and competencies. In this process, the development of metalinguistic competencies is fundamental to promote an integrated understanding of the structure and functioning of both oral and written language, essential for learning to read and write. The study addresses, in the first part, the concepts and notions of literacy and reading acquisition; in the subsequent section, it analyzes the National Literacy Policy of 2019 and its impacts on the teaching of reading and writing. In the third part, it presents metalinguistic competencies and their interrelations in the development of linguistic work in initial literacy, complemented by some pedagogical activities that enhance the development of these competencies. It is a bibliographic study with a qualitative descriptive approach, based on a dialogue with renowned scholars and researchers in the field of language who contributed to the understanding of a somewhat complex theme that requires extensive study for in-depth exploration. Among others, we cite Piccoli and Camini (2012); Soares (2017; 2020). The results indicate that initial literacy requires educators to have a solid training and mastery of the technical and pedagogical processes necessary to develop linguistic work concerning the formation of students' metalinguistic skills and competencies. It is not enough for students to encode and decode words or read short sentences; they must also advance in both understanding and producing different text genres.